Isolated intracranial hypertension associated with COVID-19 - Silva, Marcus Tulius T; Lima, Marco A; Torezani, Guilherme; Soares, Cristiane N; Dantas, Claudia; Brandão, Carlos Otávio; Espíndola, Otávio; Siqueira, Marilda M; Araujo, Abelardo QC (Cephalalgia, 2020)
Background Headache is a frequent complaint in COVID-19 patients. However, no detailed information on headache characteristics is provided in these reports. Our objective is to describe the characteristics of headache and the cerebrospinal fluid (CSF) profile in COVID-19 patients, highlighting the cases of isolated intracranial hypertension. Methods In this cross-sectional study, we selected COVID-19 patients who underwent lumbar puncture due to neurological complaints from April to May 2020. We reviewed clinical, imaging, and laboratory data of patients with refractory headache in the absence of other encephalitic or meningitic features. CSF opening pressures higher than 250 mmH2O were considered elevated, and from 200 to 250 mmH2O equivocal. Results Fifty-six COVID-19 patients underwent lumbar puncture for different neurological conditions. A new, persistent headache that prompted a CSF analysis was diagnosed in 13 (23.2%). The pain was throbbing, holocranial or bilateral in the majority of patients. All patients had normal CSF analysis and RT-qPCR for SARS-CoV-2 was negative in all samples. Opening pressure >200 mmH2O was present in 11 patients and, in six of these, > 250 mmH2O. 6/13 patients had complete improvement of the pain, five had partial improvement, and two were left with a daily persistent headache. Conclusions In a significant proportion of COVID-19 patients, headache was associated to intracranial hypertension in the absence of meningitic or encephalitic features. Coagulopathy associated with COVID-19 could be an explanation, but further studies including post-mortem analysis of areas of production and CSF absorption (choroid plexuses and arachnoid granulations) are necessary to clarify this issue.